Comparative study of wild and transformed salt tolerant bacterial strains on Triticum aestivum growth under salt stress - Afrasayab,Shazia (2010)
Eleven salt tolerant bacteria isolated from different sources (soil, plants) and their transformed strains were used to study their influence on Triticum aestivum var. Inqlab-91 growth under salt (100 mM NaCl) stress. Salt stress caused reduction in germination (19.4%), seedling growth (46%) and fresh weight (39%) in non-inoculated plants. In general, both wild and transformed strains stimulated germination, seedling growth and fresh weight in salt free and salt stressed conditions. At 100 mM NaCl, Staphylococcus xylosus ST-1 caused 25% increments in seedling length over respective control. Soluble protein content significantly enhanced (49%) under salt stress as compared to salt free control. At 100 mM NaCl parental strain PT-5 resulted about 32% enhancement in protein content over respective control treatment. Salt stress induced the promotion of auxin content in seedlings. Overall, Bacillus subtilis HAa2 and transformed E. coli-SP-7-T, caused 33% and 30% increases in auxin content, respectively, were recorded under salt stress in comparison to control.